Tinjauan Sarana dan Prasarana Bengkel Pemesinan di SMK Negeri 1 Padang - Teuku Kamal Furqan; Budi Syahri; Syahril Syahril; Andre Kurniawan (Jurnal Vokasi Mekanika (VoMek), 2025)
This article describes issue of mechanical worshop facilities and infrastructures at Vocational High School 1 Padang, aims to evaluate the availability and feasibility of facilities and infrastructure, in order to encourage learning process of mechanical engineering. This study reviews aspects related to the adequacy of mechanical workshop’s facilities and infrastructures including the existence and condition of machine, workshop space to other supporting infrastructure linked to work productivity and safety such as wall, lighting, ventilation, and floor conditions. Descriptive quantitative method was used with data collection techniques consisting of observation, interview with workshop managers, and documentation. The result revealed 87% of the facilities were classified as operational and available to support practical activities. Total percentage of feasibility for each workshop are: 90% of the lathe workshop, 77% of the miling machine workshop, 90% of the bench workshop, and 92 % of the welding and grinding machine workshop. The maximum percentage of facility feasibilities which is 100% has not been achieved, influenced by several factors related to the damage and unavailability of several items. In infrastructure, the ventilation is of standard size; lighting is appropriate and sufficient; the wall is of limited height and filled with large machines resulting in limited space for movement; the floor of the lathe workshop is inadequate with a number of cement patches on the floor cracks. Indicating the need for repairs and upgrades to increase the percentage of feasibility to maximum.